A mode-locked thulium-doped fiber laser with multiple wavelength output based on a nonlinear loop mirror - Rusdi, Muhammad Farid Mohd; Harun, Sulaiman Wadi; Yasin, Moh (Old City Publishing, 2018)
A nonlinear polarization rotation based all-fiber passively mode-locked Thulium-doped fiber laser (TDFL) is demonstrated by using a fiber loop mirror. Polarization dependent isolator and polarization controller are inserted between ports 3 and 1 of the circulator to form a fiber loop mirror and provides intensity dependent loss for the mode-locking pulse generation. The TDFL produces a multiple wavelength output centered at 1857 nm using a 5 m long thulium-doped fiber (TDF) as a gain medium as well as nonlinear medium. The mode-locked emission is obtained at threshold pump power of 857 mW with consistent pulse repetition rate of 68 MHz. Maximum pulse energy is calculated as 0.94 nJ at pump power of 1224 mW, whereas the minimum pulse width is estimated to be approximately 65 ps corresponding to sech2 pulse profile.